Analysis of Thermomechanical Stresses of a Photovoltaic Panel Using a Passive System of Cooling - Brayan L. Pérez Escobar (MDPI AG, 2021)
In this paper, the gradient temperature and the thermomechanical stresses of a photovoltaic panel has been studied with and without heatsink. For this purpose, a three-dimensional analysis was carried out. Accordingly, a heat transfer analysis was developed. The numerical results show a cooling close to 26.7% with the proposed triangle fins compared with the rectangular fins studied before by another author, and the temperature distribution was determined. With this information, the stress analysis was carried out in order to find the effect on the panel due to the thermomechanical stresses. The aluminium frame was restricted to move freely. The resulting stresses field established the magnitude of the alternative stresses, resulting in a 6.7% drop compared with a reference panel. The guidelines of IEC 61215 have to be take into account. Due to the results obtained, the use of this kind of system in desert conditions is desirable because of its high operational temperature and due to the increase in heat transfer by the fins.